Study Analysis on Knowledge, Attitude, and Behavior of Colorectal Cancer Patients: A Single-Center Observational Study at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Lukman, Kiki; Imam Rachman Hakim (Sriwijaya Journal of Surgery, 2024)
Introduction: Colorectal cancer (CRC) is the second deadliest cancer with the second highest mortality rate (9.2%) after lung cancer (11.4%) and breast cancer (6.9%). CRC is more prevalent in developed countries and more prevalent among men, with incidence rates per 100,000 in both sexes at 19.7, 23.6, and 16.3 respectively. Majority of the patients came to the hospital with diagnosis of loco regional and metastatic colorectal cancer. Therefore, information and education regarding CRC are important to the patient and their family to assure optimal screening and management. This study aimed to determine the effect of education on knowledge, attitudes, behavior of colorectal cancer patients. Methods: A descriptive-analytic research study design was conducted, including all patients diagnosed with colorectal cancer coming to Dr. Hasan Sadikin Hospital Bandung, a tertiary referral hospital, in the period August 2021 to August 2022. The pre and post-education questionnaire were used to evaluate the knowledge, attitude, and behaviour of the respondent regarding the colorectal cancer. An informational leaflet with verbal explanation was utilized as educational material. Data was analyzed using SPSS version 24. Results: Fifty-two respondents were recruited and more than half of the respondents (73.1%) showed a high mark in the post-test knowledge of CRC. Furthermore, behavior aspect also showed a dramatic increase and almost all the subjects (98.1%) scored high on behavior aspect. Conclusion: The education provided to CRC patients significantly enhances their knowledge, attitude, and behavior.